2022
DOI: 10.1002/cpz1.408
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Human Induced Pluripotent Stem Cells into Keratinocytes

Abstract: Investigating basic biological mechanisms underlying human diseases relies on the availability of sufficient quantities of patient cells. As most primary somatic cells have a limited lifespan, obtaining sufficient material for biological studies has been a challenge. The development of induced pluripotent stem cell (iPSC) technology has been a game changer, especially in the field of rare genetic disorders. iPSC are essentially immortal, can be stored indefinitely, and can thus be used to generate defined soma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…However, due to the asynchronous nature of cell division, the resulting embryoid bodies are heterogenous in size and shape. To overcome this limitation, methods exist to separately aggregate pluripotent stem cells as individual spheroids in static multi-well plates as described in previously published Current Protocols articles (Koch et al, 2022;Lewis-Israeli et al, 2022). Still, this approach can pose technical challenges for downstream handling and manipulation of these aggregates once formed.…”
Section: Understanding Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the asynchronous nature of cell division, the resulting embryoid bodies are heterogenous in size and shape. To overcome this limitation, methods exist to separately aggregate pluripotent stem cells as individual spheroids in static multi-well plates as described in previously published Current Protocols articles (Koch et al, 2022;Lewis-Israeli et al, 2022). Still, this approach can pose technical challenges for downstream handling and manipulation of these aggregates once formed.…”
Section: Understanding Resultsmentioning
confidence: 99%
“…Several methods for the culture of hPSCs have been established that utilize either undefined animal‐origin products or defined xeno‐free products. The utility of these products can be found in previously published Current Protocols articles (Gogolou, Frith, & Tsakiridis, 2021; Koch, Webb, Gugger, Salois, & Koster, 2022; Lewis‐Israeli, Abdelhamid, Olomu, & Aguirre, 2022). The differentiation protocol presented here is compatible with many different hPSC culture systems; however, we acknowledge that greater reproducibility can be achieved when using reagents that are free from the influence of animal derivatives.…”
Section: Strategic Planningmentioning
confidence: 99%
“…Further, genetic variants can be corrected in iPSC, allowing for the generation of pairs of cells that share the same genetic background, and differ only by the presence or absence of the variant. Using specialized protocols, iPSC can be differentiated into relevant somatic cell types, for example into cells of the skin, eye, or lacrimal gland (Kasal et al, 2022; Koch et al, 2022; Sareen et al, 2014). Patient‐derived iPSC‐based models have been used extensively in studies aimed at dissecting the cellular and molecular basis of skin defects in patients affected by AEC and EEC, as well as different forms of EB, and have led to important insights into the respective disease mechanisms (Coutier et al, 2022; Dinella et al, 2018; Jackow et al, 2019; Shalom‐Feuerstein et al, 2013).…”
Section: Model Systems To Advance Knowledge and Facilitate Treatment ...mentioning
confidence: 99%
“…6,15 We used a well-established protocol that relies on BMP4 and retinoic acid to differentiate iPSC into iPSC-derived keratinocytes (iPSC-K). 6,16 We previously demonstrated that these iPSC-K express marker proteins of normal human keratinocytes. 6,16 Further, using these AEC and GC iPSC-K, we identified major defects in the expression and subcellular distribution of desmosomal proteins.…”
Section: Introductionmentioning
confidence: 99%
“…6,16 We previously demonstrated that these iPSC-K express marker proteins of normal human keratinocytes. 6,16 Further, using these AEC and GC iPSC-K, we identified major defects in the expression and subcellular distribution of desmosomal proteins. 6 These defects were also observed in AEC patient skin, further validating AEC iPSC-K as a model for AEC skin.…”
Section: Introductionmentioning
confidence: 99%